PEMANFAATAN ENZIM PAPAIN DARI PEPAYA LOKAL SEBAGAI PROTEASE UNTUK ISOLASI DNA GENOME BAKTERI DALAM MENUNJANG PEMERIKSAAN POLYMERASE CHAIN REACTION (PCR) - Fini Ainun Qolbi Wasdili; Dwi Davidson Rihibiha; Ellsie Viendra Permana (LPPM Universitas Abdurrab, 2024)
Polymerase chain Reaction (PCR) is affected by many factors, one of which is DNA isolation. Proteinase K is a common protease used in DNA isolation. However, proteinase K is relatively expensive and limited. To date, many studies have been conducted to explore alternative protease from nature. Papain is an enzyme derived from papaya, which has been frequently observed, makes it promising as protease in DNA isolation. This study aims to evaluate potency of papain as cheaper alternative in DNA isolation from Salmonella thypi. This study consisted of four steps: papain extraction, characterization of papain, DNA isolation, and fliC detection with PCR. Papain was acquired with tapping method which resulted in approximately 1700 Î¼l bp. Molecular weight of papain was 23,4 kDa, and its total concentration was 903 mg/mL. Whole genom of Salmonella thypi was successfully isolated using papain. The DNA concentration was also comparable to control. Nevertheless, the purity was low which is not recommended to be used in PCR.